PERLINDUNGAN HUKUM TERHADAP PEKERJA MIGRAN INDONESIA DI FILIPINA MENURUT PERSPEKTIF HUKUM INTERNASIONAL - Zikri Agus Ibrahim YB; Phoenna Ath Thariq (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
Indonesia and the Philippines are countries that have ratified the International Convention on the protection of the right of all migrant workers and members of their families. The year 2012. This convention is the result of the United Nations' efforts to recognize that there are often inhumane acts against migrant workers so that they urgently need protection, especially for those who work abroad. The purpose in this research to find out how the protection of Indonesia migran workersin the Philippines is from perspective Internasional Convention on the Protection of The Right of All Migrant Workers and Members of Their Families and what is Indonesia’s role in protecting Indonesian migrant workers in the Philippines. This research is a normative research or library research library research, this research uses the main material, namely library material, in the form of secondary data consisting of primary legal data. explain and know about how the legal protection for Indonesian migrant workers who are in the Philippines according to the perspective of international law. The protection of migrant workers is contained in the International Convention on the protection of the right of all migrant workers and members of their families, ratified in Law no 6 of 2012 and has also been ratified by the Philippines in Law 10022. happens, requires the two countries to cooperate to protect migrant workers if violations continue to occur. It is recommended that the Indonesian government, especially the Ministry of Foreign Affairs, represented by diplomats, should continue to monitor and prioritize Indonesian migrant workers and take a policy, especially in handling and guaranteeing protection for Indonesian citizens who are taking work abroad, so as to achieve protection and guarantee the rights that they should get.